Meningkatkan Kemampuan Menerapkan Hukum Kekekalan Energi dengan Menggunakan Media Gayus di Kelas VIII.6 SMP Negeri 1 Tanjung - Sumaningsih, Ni Made Ayu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The aim of this study was to improve the ability to apply the energy conservation law by using Gayus media in class VIII.6 of SMPN 1 Tanjung. This research used a classroom action research consisting of 2 cycles of action. Each cycle consisted of four stages including planning, implementing, observing the results of actions, and reflecting. Data collection technique of the study used observation and tests. Data analysis of the research used descriptive quantitative analysis technique. The results of the study showed that the use of Gayus media could improve students’ ability to apply the energy conservation law. The pre-test average score was 68.7 with the classical completeness percentage reached 40%. Meanwhile, the post-test average score had increased to 75.2 with the classical completeness percentage reached 73.3%. The increase in average value was 33.3%. The average score of process skills in cycle was I 69.1 and cycle II was 80.5. Scientific performance improvement was 11.4